Synthesis and Antitubercular Evaluation of Diverse Glycosylated Ureas from D-Glucose - Neetu Tripathi; Vinod K. Tiwari (Journal of Chemistry)
Dedicated to Dr. Rama P. Tripathi, Former Chief Scientist at CSIR-Central Drug Research Institute, Lucknow, India, for his extraordinary contribution to “Drug development against Tuberculosis”